Variants of plasma lipoprotein profile in persons with maladaptation - Liliya Barylyak; Volodymyr Tsymbryla; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2015)
Introduction and aim. Atherogenic lipoprotein profile of plasma is an important risk factor for coronary artery disease. It is characterized by high ratio of logarithm of triglycerides (TG) to high-density lipoprotein cholesterol (HDL-Ch) called as "atherogenic index of plasma" (AIP). AIP reflect the actual composition of the lipoprotein spectrum and thus predict both the cardiovascular risk and effectiveness of therapy. This article initiates the project "Relationships between plasma lipoprotein profile and neuroendocrine-immune complex parameters and the influence on them of the factors of the Truskavets' spa". The first goal is the formation of homogeneous cluster groups. Material and methods. The object of observation were 41 volunteers: 20 women aged 30-76 years and 21 men aged 24-69 years without clinical diagnose but with dysfunction of neuroendocrine-immune complex and metabolism, characteristic for maladaptation. We estimated lipoprotein profile of plasma: total cholesterol level and its content in composition of HDL, VLDL and LDL. Based on them, two AIPs were calculated: TG/HDL-Ch named as Dobiásová&Frohlich as well as previously widely used Klimov's AIP as ratio (VLDLCh + LDLCh)/HDLCh. Results. Using the method of cluster analysis, the sample was divided into 5 homogeneous groups, different from each other. It was found that 11 members of the V cluster, the oldest in the sample, exclusively women, had the maximum for sampling increased total Cholesterol, HDL-Ch and Triglycerides levels. At the opposite pole localized 11 members of I cluster, the youngest in the sample, in whom the levels of listed variables as well as LDLCh and Dobiásová&Frohlich AIP was decreased and gender representation was almost the same. The intermediate positions of the members of the other three clusters reflect, as a rule, the intermediate levels of the listed variables. A characteristic feature of 7 members of IV cluster was the maximally increased levels of both Dobiásová&Frohlich's and Klimov's AIP. The age and sex together determines Dobiásová&Frohlich's AIP on 34%. Overall classification accuracy by 6 discriminant variables is 96,3%. Conclusion. The plasma lipoprotein profile of persons with maladaptation is characterized by a wide range of values, from increased to decreased. This should be kept in mind during the next study of its connections with the parameters of the neuroendocrine-immune complex.